2001
DOI: 10.1116/1.1338555
|View full text |Cite
|
Sign up to set email alerts
|

Laser reflectometryin situmonitoring structural and growth effects on the electron cyclotron resonance etching of In0.49Ga0.51P layers in Al-free laser structures

Abstract: Electron cyclotron resonance (ECR) plasma etching of p- and n-In0.49Ga0.51P layers in Al-free laser structures is studied based on BCl3/N2 gas mixture. Laser reflectometry is used for the in situ etching analysis. Strong etching rate discrepancies are found for the same material whether inserted in multilayer laser structures or in single calibration layers. Strong etching dependence with growth conditions and beryllium concentration is found. Great reduction in etching rate is observed near p++GaAs/p++In0.49G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Also, a reduction in beryllium doping efficiency is observed as the growth temperature increases from 500 C to 540 C. Associated with the reduction in beryllium doping efficiency, it is always observed surface morphology degradation by atomic force microscopy and a direct relationship to an increased electrochemical etching pit density [7]. An anomalous reduction in BCl 3 etching rate has been observed in ''in situ'' optically monitored dry process of highly Be-doped layers being related to BeCl 3 formation [8]. Finally, it has been shown that Be 3 P 2 can be synthesized by the direct reaction of phosphorus vapor with metallic beryllium at 700 C [9].…”
Section: Introductionmentioning
confidence: 91%
“…Also, a reduction in beryllium doping efficiency is observed as the growth temperature increases from 500 C to 540 C. Associated with the reduction in beryllium doping efficiency, it is always observed surface morphology degradation by atomic force microscopy and a direct relationship to an increased electrochemical etching pit density [7]. An anomalous reduction in BCl 3 etching rate has been observed in ''in situ'' optically monitored dry process of highly Be-doped layers being related to BeCl 3 formation [8]. Finally, it has been shown that Be 3 P 2 can be synthesized by the direct reaction of phosphorus vapor with metallic beryllium at 700 C [9].…”
Section: Introductionmentioning
confidence: 91%